2014
DOI: 10.1016/j.yexcr.2013.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Chorion formation in panoistic ovaries requires windei and trimethylation of histone 3 lysine 9

Abstract: Epigenetic modifications play key roles in transcriptional regulation. Trimethylation of histone 3 lysine 9 (H3K9me3) is one of the most widely studied histone post-translational modifications, and has been linked to transcriptional repression. In Drosophila melanogaster, Windei is needed for H3K9me3 in female germ line cells. Here, we report the occurrence of a D. melanogaster Windei (Wde) ortholog in the ovary of the hemimetabolous insect Blattella germanica, which we named BgWde. Depletion of BgWde by RNAi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 29 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Wde is an essential co-factor of Egg [59]. There is one predicted homolog of wde in the cockroach genome annotation (BGER025676), but an independently sequenced cockroach wde gene (CCX34999) is longer than the wde homolog predicted by the automated annotation [60]. We therefore compared CCX34999 with D. melanogaster Wde.…”
Section: Resultsmentioning
confidence: 99%
“…Wde is an essential co-factor of Egg [59]. There is one predicted homolog of wde in the cockroach genome annotation (BGER025676), but an independently sequenced cockroach wde gene (CCX34999) is longer than the wde homolog predicted by the automated annotation [60]. We therefore compared CCX34999 with D. melanogaster Wde.…”
Section: Resultsmentioning
confidence: 99%
“…In Diploptera punctata , the expression patterns also suggested that Fcp3C plays a role in chorion formation [22,23]. Furthermore, failure in forming chorion layers caused by depletion of Bg Windei by RNAi was coupled with significant underexpression of Fcp3C [24]. However, there is no direct evidence to prove the function of Fcp3C.…”
Section: Discussionmentioning
confidence: 99%
“…Wde is an essential co-factor of Egg [58]. There is one predicted homolog of wde in the cockroach genome annotation (BGER025676), but an independently sequenced cockroach wde gene (CCX34999) is longer than the wde homolog predicted by the automated annotation [59]. We therefore compared CCX34999 with D. melanogaster Wde.…”
Section: Conservation Of Element F Transcriptional Regulators In Cockmentioning
confidence: 99%